Comparison of the heart failure risk stratification performance of the CKD–EPI equation and the MDRD equation for estimated glomerular filtration rate in patients with Type 2 diabetes. Issue 5 (30th August 2015) - Wang, Y.; Katzmarzyk, P. T.; Horswell, R.; Zhao, W.; Johnson, J.; Hu, G.
Abstract: Aims: To investigate the risk prediction and the risk stratification performances of the Chronic Kidney Disease Epidemiology Collaboration (CKD–EPI) equation and the Modification of Diet in Renal Disease (MDRD) equation for estimated glomerular filtration rate (eGFRCKD – EPI vs. eGFRMDRD ) on heart failure in patients with Type 2 diabetes. Methods: The study cohort included 12 258 White and 16 886 African American low‐income patients with Type 2 diabetes who were 30–90 years old at baseline. Heart failure risk according to different eGFRCKD – EPI and eGFRMDRD categories was prospectively assessed. Results: During a mean follow‐up of 6.5 years, 5043 incident heart failure cases were identified. Multivariable‐adjusted hazard ratios (HRs) of heart failure associated with the eGFRCKD – EPI categories [≥ 90 (reference group), 75–89, 60–74, 30–59 and < 30 ml/min/1.73 m 2 ] were 1.00, 1.11, 1.31, 1.75 and 2.93 ( P trend < 0.001) for African American patients, and 1.00, 1.11, 1.08, 1.59 and 2.92 ( P trend < 0.001) for White patients, respectively. The model with eGFRCKD – EPI and the other risk factors had significantly higher Harrell's C than the model with eGFRMDRD and other risk factors. Patients reclassified downward from eGFRMDRD 60–74 to eGFRCKD – EPI 30–59 and from eGFRMDRD 30–59 to eGFRCKD – EPI < 30 ml/min/1.73 m 2 showed higher heart failure risk than those who were not reclassified. Conclusions: Impaired kidney function (i.e. GFR < 60 ml/min/1.73 m 2 ), and even mildly decreased GFR (60–74 ml/min/1.73 m 2 ) estimated by both equations is associated with an increased risk of heart failure. Compared with GFR estimated using the MDRD equation, GFR estimated using the CKD–EPI equation added more predictive power to the model with the other risk factors. Also, eGFRCKD – EPI provided more accurate heart failure risk stratification than eGFRMDRD . What's new?: The is the first large prospective study to assess the risk prediction and risk stratification performances of the Chronic Kidney Disease Epidemiology Collaboration (CKD–EPI) equation and the Modification of Diet in Renal Disease (MDRD) equation for estimated glomerular filtration rate ((eGFRCKD–EPI vs. eGFRMDRD ) on heart failure in low‐income patients with Type 2 diabetes. The study showed that impaired kidney function (i.e. GFR < 60 ml/min/1.73 m 2 ), and even mildly decreased GFR (60–74 ml/min/1.73 m 2 ) estimated by both equations is associated with an increased risk of heart failure. Compared with eGFRMDRD, eGFRCKD–EPI adds more predictive power to a model with only conventional covariates. Also, eGFRCKD–EPI may provide more accurate heart failure risk stratification than eGFRMDRD .